2018
DOI: 10.1111/ejn.14113
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of proliferative, glial and angiogenic responses after a CoCl2‐induced injury of photoreceptor cells in the adult zebrafish retina

Abstract: The adult zebrafish is considered a useful model for studying mechanisms involved in tissue growth and regeneration. We have characterized cytotoxic damage to the retina of adult zebrafish caused by the injection of cobalt chloride (CoCl ) into the vitreous cavity. The CoCl concentration we used primarily caused injury to photoreceptors. We observed the complete disappearance of cones, followed by rods, across the retina surface from 28 to 96 hr after CoCl injury. The loss of 30% of bipolar cells was also obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 53 publications
(81 reference statements)
8
21
0
Order By: Relevance
“…The injury mechanism of the retina has shown a wide range of variations ranging from whole‐cell retinal injury to exploiting each layer individually viz. photoreceptor, 9 , 10 , 11 ganglionic layer, 12 etc, using light, chemicals, transgenic lines, and genetic ablations. Various injury methods were applied with the following aims: To determine where the regeneration capacity lies within the retina.…”
Section: Mechanisms Of Retinal Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…The injury mechanism of the retina has shown a wide range of variations ranging from whole‐cell retinal injury to exploiting each layer individually viz. photoreceptor, 9 , 10 , 11 ganglionic layer, 12 etc, using light, chemicals, transgenic lines, and genetic ablations. Various injury methods were applied with the following aims: To determine where the regeneration capacity lies within the retina.…”
Section: Mechanisms Of Retinal Injurymentioning
confidence: 99%
“…Introduced by Maier and Wolberg in 1979, 42 it can destroy the whole retina 43 when used in high doses, and intravitreal injection of lower doses is efficient in targeting different individual layers such as the inner nuclear layers, 44 amacrine layers, 12 and photoreceptors. 11 , 42 The injury mechanism usually follows a microknife for incision followed by injection of ouabain in the intravitreal cavity.…”
Section: Mechanisms Of Retinal Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…The literature has many examples, detailed below; however, 70% of those studies have been reported only during the past 5 years, indicating that the use of the model in this field is still in its larval stage. Outside of chemical toxicology, zebrafish studies focused on eyes are also adding to our understanding of radiation toxicity, 150,151 ocular diseases, [152][153][154] retinal genetics and regeneration, [155][156][157][158] as well as aiding therapeutic discovery. [159][160][161] An exception among areas of ocular toxicology studied using zebrafish is how ethanol effects the developing embryo; this has been studied for more than 40 years.…”
Section: Chemical Toxicity Researchmentioning
confidence: 99%
“…We have previously described a model of retinal degeneration that primarily involves photoreceptor death across the surface of the retina of zebrafish (Medrano et al, 2018). The injury model consisted in injecting a single dose of CoCl2 within the vitreous cavity.…”
Section: Introductionmentioning
confidence: 99%